Kansei innovation : practical design applications for product and service development - Nagamachi, Mitsuo, 1936- (Industrial innovation series., 2015)
"The idea of Kansei engineering was conceived in 1970. Since then, the founder has worked to establish the Kansei engineering methodology and has created more than fifty new product developments. Kansei engineering research is gaining popularity in many countries"--